A case–control study on the individualized use of opioid analgesics based on single-nucleotide polymorphism - Yang, Jing; Zheng, Lei; Zheng, Fu; Zhou, Shu-Han; Sun, Liang-Wei; Song, Chao (Frontiers in Pharmacology, 2025)
ObjectiveThe aim of this study is to explore the relationship between gene polymorphism and the efficacy and adverse drug reactions (ADRs) of opioid analgesics, improve medication safety, and promote personalized medication.MethodsFirst, the method of evidence-based medicine retrieval and evaluation was adopted to systematically summarize the opioid analgesic drug ADR and efficacy-related gene loci currently recommended by guidelines, authoritative genetic information databases, and low-bias clinical trial studies. The gene loci with strong correlation evaluation were selected as target genes for testing. Then, a clinical case–control trial was designed, divided into two groups: the ADR research group and the dose demand research group. A total of 480 enrolled patients were tested for target genes. Finally, the gene test results were evaluated for ADR association and drug dose association using SPSS 26.0 software and the SNPStats tool.ResultsFour genes were selected for detection: CYP2D6, CYP3A5*3, ABCB1, and OPRM1. The results of the correlation analysis showed that, in the ADR research group, compared with the control subgroup, the AG + GG type distribution of OPRM1 (rs1799971, A>G) was lower, and the AA type distribution was higher in the observation subgroup (P < 0.05). Individual statistics of patients using oxycodone also revealed differences in OPRM1 (rs1799971, A>G). In particular, in the observation subgroup, the AA type accounted for 56.35% and the AG + GG type accounted for 43.65%; in the control subgroup, the AA type accounted for 38.28% and the AG + GG type accounted for 61.72%; compared with the control subgroup, the proportion of OPRM1 (rs1799971, A>G) AA type was higher in the experimental subgroup (P < 0.05). The SNPStats program was used to analyze the association between single-nucleotide polymorphism (SNP) and ADR in five genetic models. The results showed that co-dominant, dominant, and allele models all suggested a significant association between OPRM1 (rs1799971) and ADR incidence (P < 0.05). In the dose demand evaluation group, the results showed that there was no significant difference in genotype distribution between the observation subgroup (high-dose group) and the control subgroup (low-dose group) (P > 0.05). However, attention should be paid to the ABCB1 gene. At the current sample size, the ABCB1 (rs1045642, C>T) CC + CT ratio in the observation subgroup tends to be higher than that in the control subgroup compared to TT.ConclusionOPRM1 (rs1799971) AA genotype patients have a higher risk of ADR. OPRM1 AA genotype patients should pay more attention to ADR, and the dosage can be initiated at low levels. The association between dose demand and SNPs still needs to be evaluated in larger cohorts. Meanwhile, particular attention should be given to the ABCB1 gene.